Participatory Practices in the Energy Transition in Italy: Toward a Co-Productionist, Situated, and Relational Perspective - Musolino, Monica (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
The contribution aims to analyze the emerging forms of participation in energy transition processes in relation to the transformations occurring in the territories alongside these changes. Essentially, it seeks to understand how the vision and actual landscape of diverse territories are evolving in response to the spread of new socio-technical participatory practices and configurations for managing energy from renewable sources. The theoretical-methodological framework used to develop this analysis is based on the relational STS (Science Technology Society) approach, which views participation in the ecological transition as a co-construction phenomenon involving the social, economic, political, and cultural context. Based on this theoretical framework and considering the major transformative trends that have affected the energy market and system in recent decades, the analysis focuses on certain co-construction processes between participation in the energy transition and the transformation of emerging territories in Europe, especially in Italy, offering a broad and open classification into strategic actions and tactical actions. This defined polarity allows the emphasis to be placed on a case study of a solidarity energy community and urban transformation, currently unfolding in a marginalized neighborhood in Messina. This case is considered as one of the examples of similar processes, some already underway, that in the coming years will have development potential in vulnerable areas of Southern Italy. Indeed, these areas are also the focus of public policies, particularly aimed at halting depopulation in inland centers or promoting urban regeneration in marginalized neighborhoods, in order to foster possible development centered on the role of the local community and on economic, environmental, and social sustainability.